2021
DOI: 10.1186/s12963-020-00225-0
|View full text |Cite
|
Sign up to set email alerts
|

Four decades of measuring stillbirths and neonatal deaths in Demographic and Health Surveys: historical review

Abstract: Background Worldwide, an estimated 5.1 million stillbirths and neonatal deaths occur annually, 98% in low- and middle-income countries. Limited coverage of civil and vital registration systems necessitates reliance on women’s retrospective reporting in household surveys for data on these deaths. The predominant platform, Demographic and Health Surveys (DHS), has evolved over the last 35 years and differs by country, yet no previous study has described these differences and the effects of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Third, while we hypothesize that improved quality of care in hospitals may be a key factor for the observed associations, limited cross-country data on quality of care prevent direct measurement. Finally, this analysis did not consider stillbirths as an outcome because they were inconsistently recorded in versions of the DHS that relied on a full birth history rather than a full pregnancy history [ 33 ]; neonatal deaths by cause were also not considered as that information is unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Third, while we hypothesize that improved quality of care in hospitals may be a key factor for the observed associations, limited cross-country data on quality of care prevent direct measurement. Finally, this analysis did not consider stillbirths as an outcome because they were inconsistently recorded in versions of the DHS that relied on a full birth history rather than a full pregnancy history [ 33 ]; neonatal deaths by cause were also not considered as that information is unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Though other estimates of crude birth rates for Rohingya refugees are available we used the DHS estimate 9. The DHS has robust methodology to estimate crude birth rates, using pregnancy history, and is the standard in global health 18. Total births were calculated as the sum of the estimated live births described and stillbirths captured through our community-based surveillance.…”
Section: Methodsmentioning
confidence: 99%
“…This is due, in large part, to complex methodological challenges in the acute phase of a humanitarian crisis. In the absence of civil registration of vital events (ie, births, deaths), low-income and middle-income countries depend on household surveys, such as the Demographic and Health Survey (DHS), to estimate neonatal mortality 17 18. The DHS uses full birth history and/or full pregnancy history as recalled retrospectively by the respondent that captures data from women of reproductive age on their pregnancies and pregnancy outcomes 18.…”
Section: Introductionmentioning
confidence: 99%
“…Because vital registration systems in many countries are underdeveloped, sample surveys are often used to understand population health trends. However, sample surveys like the Demographic and Health Survey (DHS) have been inconsistent in recording stillbirth (Bradley et al 2015, MacQuarrie et al 2018, Akuze et al 2020, Akuze et al 2021. In a recent study looking across DHS surveys between 2005 and 2015, Christou et al (2017) found that many different methods are used to collect data on pregnancy loss.…”
Section: Stillbirth In the Demography Literaturementioning
confidence: 99%